Functional outcomes of extra-articular distal radius fracture using T-buttress plate - Rashid, Haroon; Mahmood, Khalid; Khan, Shaukat Hayat; Arra, Iffat; Summyia, . (Biological and Clinical Sciences Research Journal, 2025)
Extra-articular distal radius fractures are common upper limb injuries, and optimal surgical intervention remains debated. While Kirschner’s wire (K-wire) fixation is traditionally used, volar locking plates such as the T-butterfly (T-buttress) plate offer potentially superior outcomes. Objective: To assess the functional outcome of extra-articular distal radius fractures treated with T-buttress volar locking plate compared to closed reduction and K-wire fixation. Methods: This quasi-experimental study was conducted at SKBZ/CMH Muzaffarabad after obtaining ethical approval from January to July 2023. A total of 70 patients aged 20–40 years with extra-articular distal radius fractures were randomized into two equal groups: Group T (open reduction and internal fixation with T-buttress volar locking plate) and Group K (closed reduction and K-wire fixation followed by plaster immobilization). Functional outcomes were evaluated at 20 weeks postoperatively using a standardized scoring system. Results: In Group T, 12 patients (34.3%) had excellent outcomes, 20 (57.1%) had good outcomes, and 3 (8.6%) had fair outcomes, with no poor outcomes reported. In Group K, two patients (5.7%) had excellent outcomes, 18 (51.4%) had good outcomes, 12 (34.3%) had fair outcomes, and three patients (8.6%) had poor outcomes. Functional outcomes were significantly better in Group T compared to Group K (p < 0.05). Conclusion: The use of T-buttress volar locking plate for the fixation of extra-articular distal radius fractures provides superior functional outcomes with fewer complications compared to K-wire fixation. It should be considered a preferred method of surgical management for such fractures in young adults.